An Homeric Suggestion (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
The adjective hygies, from which Hygieia is derived, remains an etymological mystery. None of the various proposals from its etymology has avoided the temptation of referring to the only use by Homer of hygies in a single line (Il. 8, 524) eliminated by Aristarchus of Samothrace, as a sort of "rejected marble" like the beautiful head of Hygieia in the “Terme Milano” in Gortys.
Keywords: Etymology; Homer; Hygieia